HUBUNGAN DEGRADASI RUMINAL BAHAN KERING PROTEIN KASAR DAN SERAT KASAR BAGGASE AMONIASI UREA DITAMBAH SUMBER UREASE - Dewi Febrina (Jurnal Peternakan, 2005)
This research was conducted to know the correlation of rumina I degradation between dry matter, crude protein and crude fiber content of urea-ammoniated baggase with urease. Two fistUled of Aceh bulls weight 200 kg and 5.5 years old which were fed twice of day by 25 -30 kg of Brachiaria sp. Determination of nutrient degradation was done by in-situ technique, 5 grams sample urea~ammoniated baggase with urease was placed into nylon bag (Monil T 120, 14 x 8 cm) with 0, 6, 14 24, 48 and 72 hours of incubation.. The result showed that there was possitive correlation and differently significant (r"" 0.995 ; p< 0.01) between dry matter, crude protein and crude fiber degradation of urea-ammoniated baggase with urease. Chemical composition also .affected dry matter, crude protein dan crude fiber degradation of urea-ammoniatedbaggase with urease.